The Role of Local Economic Innovation, Education, and Health in Poverty Alleviation in Parepare City - Fitriani Fitriani; Muhammad Hatta; Jurhana Jurhana (Economos : Jurnal Ekonomi dan Bisnis, 2025)
Local economic innovation is a strategic effort to optimize regional potential in order to improve community welfare. Through the development of leading products based on local wisdom, communities can create added value and expand market access. Thus, local economic innovation plays an important role in strengthening regional competitiveness while promoting sustainable economic growth. This study aims to analyze the effect of the dependency ratio, government expenditure on education, and government expenditure on health on the poverty level in Parepare City, as well as to explore the role of local economic innovation in poverty alleviation. The method used is descriptive quantitative with secondary time series data from 2014–2019. Data analysis was carried out using multiple linear regression with SPSS 16. The results show that the dependency ratio has a positive and significant effect on poverty levels, while government expenditure on education and health has a negative and significant effect on poverty levels. In addition, local economic innovations such as strengthening MSMEs, utilizing regional leading sector potentials, and entrepreneurship training based on local resources have proven to play an important role in creating community economic independence and accelerating sustainable poverty reduction. Therefore, poverty alleviation strategies in Parepare City need to be integrated with innovative and participatory local economic development approaches to inclusively improve community welfare.